2011
DOI: 10.1117/1.3556723
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing variability in in vivo Raman spectra of different anatomical locations in the upper gastrointestinal tract toward cancer detection

Abstract: Abstract. Raman spectroscopy is an optical vibrational technology capable of probing biomolecular changes of tissue associated with cancer transformation. This study aimed to characterize in vivo Raman spectroscopic properties of tissues belonging to different anatomical regions in the upper gastrointestinal (GI) tract and explore the implications for early detection of neoplastic lesions during clinical gastroscopy. A novel fiber-optic Raman endoscopy technique was utilized for real-time in vivo tissue Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 41 publications
5
84
0
2
Order By: Relevance
“…Some were commonly used in skin and non-skin models. For instance, collagen and triolein are known to be important contributors to the RS signal of breast, gastric, and artery tissues [17,19,20]. We demonstrated these two components also played an important role for fitting in vivo skin data.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Some were commonly used in skin and non-skin models. For instance, collagen and triolein are known to be important contributors to the RS signal of breast, gastric, and artery tissues [17,19,20]. We demonstrated these two components also played an important role for fitting in vivo skin data.…”
Section: Discussionmentioning
confidence: 91%
“…The building blocks of our model are Raman active components extracted from skin in situ. Previous biophysical models used model components either measured directly from synthetic/purified chemicals [9,[15][16][17][18], or extracted from tissue sections in situ [19][20][21]. The advantage of using synthetic/purified chemicals as model components is that they can be easily measured without the need for Raman micro-imaging.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Also, in vivo Raman applications to achieve better diagnostic results for dysplastic diseases have been reported. 13 In contrast, little has been reported about using Raman spectroscopy to detect molecular changes taking place in epithelial cells during inflammatory conditions. A recently published study from Bi et al 14 demonstrated for the first time the potential of Raman spectroscopy (in particular fiber-optic Raman spectroscopy) in IBD by showing that Raman band heights differ for UC and CD.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational spectroscopy provides the means to non-destructively assess the molecular composition of subcellular structures [1][2][3], trace metabolic and functional processes [4,5], and identify disease [6][7][8]. A variety of different methods have been demonstrated for extracting the molecular information, each with different characteristics (see Ref [9] for a recent review).…”
Section: Introductionmentioning
confidence: 99%